2018
DOI: 10.1038/s41598-018-35292-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of a novel form of silicon supplement

Abstract: In this study, we assessed uptake and potential efficacy of a novel, pH neutral form of silicon supplement in vitro and using broiler chickens as a model species. In vitro bioavailability of this supplement was significantly higher than other commercial supplements tested, all of which claim available silica content. To confirm bioavailability of the new supplement in vivo, a broiler chick feeding trial reported blood uptake that was significantly higher than a Bamboo-derived silicon supplement. We assessed do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
17
0
2
Order By: Relevance
“…Fracture force at breaking was similar across treatments, mirroring previous findings in turkeys and rats [45], as well as water silicon supplementation to broilers [27]. However, these findings contradicted other studies showing greater breaking strength in silicon-supplemented animals [26,28,57]. This disparity was likely due to differences between four-point and threepoint bending in bone mechanical testing [58] as three-point bending generates high shear stress and four-point bending ensures almost no shear stress where loading is applied [36].…”
Section: Plos Onesupporting
confidence: 72%
See 3 more Smart Citations
“…Fracture force at breaking was similar across treatments, mirroring previous findings in turkeys and rats [45], as well as water silicon supplementation to broilers [27]. However, these findings contradicted other studies showing greater breaking strength in silicon-supplemented animals [26,28,57]. This disparity was likely due to differences between four-point and threepoint bending in bone mechanical testing [58] as three-point bending generates high shear stress and four-point bending ensures almost no shear stress where loading is applied [36].…”
Section: Plos Onesupporting
confidence: 72%
“…Other studies used much higher rates of supplementation. In the study by Scholey et al [26], bone strength was improved in birds supplemented approximately 45 mg silicon/kg BW, and tibia ash was increased in birds receiving a minimum 7.7 mg silicon/kg BW. Nakhon et al [28] showed increased tibia breaking strength in birds supplemented 12.7 mg silicon/kg BW but not in birds supplemented 17.8 mg silicon/kg BW.…”
Section: Plos Onementioning
confidence: 95%
See 2 more Smart Citations
“…Следует отметить, что классические кишечные адсорбенты на основе угля и глины имеют противопоказания к применению при эрозивно-язвенных поражениях ЖКТ. Кроме того, при пероральном использовании соединений кремния не исключено его накопление в органах и тканях [14]. В то же время ПМСПГ не обладает такими побочными эффектами, что позволяет применять его при заболеваниях ЖКТ, в том числе сопровождающихся эрозивно-язвенными поражениями слизистой оболочки [15].…”
unclassified